CAN ZONING REGULATION SIMPLIFY BUSINESS LICENSING IN INDONESIA? - Ni Nyoman Juwita Arsawati; Luh Putu Yeyen Karista Putri; I Gusti Ayu Eviani Yuliantari; Lourenco de Deus Mau Lulo (Universitas Syiah Kuala, 2023)
Law No. 6 of 2023 concerning Job Creation Law (JCL), has little attention, specifically on the impact of zoning to business licensing in Indonesia. This study applies a normative legal method with a comparative approach to assess zoning in Indonesia and East-Timor. Despite differences in the extent of areas, both countries have undertaken spatial planning integration. Zoning is part of spatial planning made by local governments to determine land allotment. Prior to the JCL, spatial planning was not integrated. The results show that zoning integration provides transparency which can simplify business licensing. However, locating zoning at the local level creates disparity. Public participation is vital to ensure that zoning accommodates development needs without neglecting environmental and safety considerations. Local governments must implement zoning properly by encouraging compliance, improving violation detection, and imposing administrative/ criminal sanctions.